Kinematic Analysis and Performance of a Planar 3RRR Parallel Robot with Kinematic Redundancy using Screw Theory (2018)
In this paper, a complete kinematic analysis of a planar 3-RRR parallel robot is presented. The position through the direct and inverse kinematics, velocities, jacobians and accelerations were developed using Screw Theory. Likewise, the workspace and singularities analysis is performed to find the smallest set of active joints for which the planar 3-RRR parallel robot remains equilibrated with respect to dexterous workspace, when failure occurs for one arbitrary active joint in a safe region. In order to accomplish this, sensitivity analysis for a classic trajectory and performance indexes for redundant planar 3-RRR parallel robot were obtained and compared with the same generation of non-redundant one, to validate the dexterity and manipulability of the mechanism. The simulation results show the maps of the dexterous workspace which the End-Effector can reach when there is redundant or non-redundant kinematics in the robot. © 2018 IEEE.